2014
DOI: 10.4236/crcm.2014.35062
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Retropharyngeal Haematoma in a One-Year-Old Child: A Case Report

Abstract: Spontaneous retropharyngeal haematoma is an unusual condition and difficult to diagnosis early especially in infants. It has multiple aetiological factors and can present to a number of specialists including the otolaryngologist. We describe an unusual case of a spontaneous huge retropharyngeal haematoma in 1-year-old male child which demonstrates the dramatic presentation and emphasizes the need for immediate surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…1 Mundra et al reported a case of spontaneous retropharyngeal hematoma where transoral surgical drainage was necessary for the management of the case. 8 This shows that the condition has to be managed according to the severity of the symptoms. If there is no airway compromise, then medical management can be attempted.…”
Section: Discussionmentioning
confidence: 99%
“…1 Mundra et al reported a case of spontaneous retropharyngeal hematoma where transoral surgical drainage was necessary for the management of the case. 8 This shows that the condition has to be managed according to the severity of the symptoms. If there is no airway compromise, then medical management can be attempted.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the bony cervicothoracic spine located posteriorly cannot bulge. As the anterior bulge increases, clinical manifestations such as neck pain, 2,3 limited neck movement, 3,4 pain on swallowing, 2,[4][5][6] stridor with respiratory distress [4][5][6][7][8][9][10] or, in extreme circumstances of bleeding, Capp's triad 5,11,12 may ensue.…”
Section: Introductionmentioning
confidence: 99%
“…These include retropharyngeal cellulitis and abscesses, 13,14 retropharyngeal oedema seen in multisystem inflammatory syndrome in children (MIS-C) 15 and Kawasaki disease, 16 thoracic duct cysts 17 or retropharyngeal haematomas. 6,8 The cases of retropharyngeal haematomas are often associated with foreign body ingestion or anticoagulation but spontaneous retropharyngeal haematomas are relatively rare. 6,8 These differential diagnoses are distinguished by radiological investigations like radiographs, CT scans and MRIs, which also aid in monitoring of disease progress.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations